1994
DOI: 10.1016/0735-1097(94)90865-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycarditis and cardiotropic viral infection associated with severe left ventricular dysfunction in late-stage infection with human immunodeficiency virus

Abstract: This study demonstrates that cardiotropic virus infection and myocarditis may be important in the pathogenesis of symptomatic HIV-associated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(74 citation statements)
references
References 32 publications
4
68
1
1
Order By: Relevance
“…However, in situ hybridiza tion or polymerase chain reaction studies reveal a high frequency of either cytomegalovirus or HIV-1 or both, in AIDS patients with lympho cytic myocarditis and severe left ventricular dys function 11,15 .These data support the hypothe sis that, at least in a subset of patients, HIV-1 has a pathogenetic action and possibly influences the clinical evolution toward dilated cardiomyopa thy. HIV-1 nucleic acid sequences were detected at autopsy by in situ DNA hybridization in 35% of the GIS CA patients with cardiac involvement; 86% of them had active myocarditis at histological ex amination 11 .…”
Section: Viral Myocarditissupporting
confidence: 75%
See 1 more Smart Citation
“…However, in situ hybridiza tion or polymerase chain reaction studies reveal a high frequency of either cytomegalovirus or HIV-1 or both, in AIDS patients with lympho cytic myocarditis and severe left ventricular dys function 11,15 .These data support the hypothe sis that, at least in a subset of patients, HIV-1 has a pathogenetic action and possibly influences the clinical evolution toward dilated cardiomyopa thy. HIV-1 nucleic acid sequences were detected at autopsy by in situ DNA hybridization in 35% of the GIS CA patients with cardiac involvement; 86% of them had active myocarditis at histological ex amination 11 .…”
Section: Viral Myocarditissupporting
confidence: 75%
“…The GISCA autopsy records show that 83% of patients with myocarditis and 50% of those with dilated cardiomyopathy were coinfected with cardiotropic vi ruses (usually, coxsackievirus B3 and cytomega lovirus 11 ). Herskowitz et al used in situ hybrid ization to detect myocardial cytomegalovirus infection in 48% of HIV-infected patients with myocarditis and left ventricular dysfunction who underwent endomyocardial biopsy 15 . Bowles et al used polymerase chain reaction and found that 42% of HIV-infected patients with cardiomy opathy had cytomegalovirus or adenovirus in the myocardial tissue 16 .…”
Section: Viral Myocarditismentioning
confidence: 99%
“…The literature regarding the cardiac cell-type specificity of infection by HIV-1 is currently unclear, with both mononuclear cells and cardiomyocytes having been reported to be infected. [23][24][25][26][27][28][29][30] However, our present results suggest that cardiomyocyte expression of HIV-1 gene products may not be necessary for the development of HIV-1-associated cardiomyopathy in humans.…”
Section: Development Of Cardiac Lesions In Tg Mice Occurs In the Absecontrasting
confidence: 44%
“…12,13 Active CMV infection has been associated with higher rates of severe allograft rejection and cardiac dysfunction, in heart transplant recipients and patients with AIDS, respectively. 14,15 Heart transplant recipients experiencing a primary CMV infection during transplantation have a 46% incidence of developing myocarditis, 16 while 50-65% of patients with active myocarditis have been found to be positive for CMV DNA in heart tissues. 17 In addition, myocardial damage post-CMV infection may persist in immunocompromised patients and lead to dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%